Fluorescence Labeling of Amino Acids and Peptides with 7-Aminocoumarins - Wirtz, Lisa; Auerbach, Dagmar; Jung, Gregor; Kazmaier, Uli (Synthesis, 2012)
Pechmann condensation is a straightforward protocol for the synthesis of alkynyl- and azido-substituted 7-(dialkylamino)coumarins, which can be coupled to amino acid and peptide derivatives by copper-catalyzed [3+2]-cycloaddition (click reaction) in high yield. This allows the introduction of these efficient fluorescence labels into biologically relevant molecules.
Keywords: amino acids; click chemistry; cycloaddition; coumarins; fluorescence labeling; peptides